EDUCATION POLICY: DIRECTION DETERMINANT IN SOLVING EDUCATIONAL PROBLEMS - Asep Suhana; Ricky Ekaristy Purwadi; Artini Bastianti (Adisam Publisher, 2024)
A set of laws or regulations known as education policy govern the way the educational system is implemented, including the objectives of education and the methods by which they are to be met. There are still a number of prevalent educational issues that make it difficult to raise the standard and accessibility of education. Of fact, a country's progress depends on its ability to provide quality education. Understanding what is meant by education policy, what it entails, what kinds of government policies are in the field of education, and how education policy is carried out are issues that frequently crop up in the context of national education policy. In order to ensure that educational activities proceed as planned and meet the desired outcomes, national education policy is crucial in safeguarding and supervising them. The research methodology employed in this study is library research, which is defined as research activities conducted by gathering information from books, journals, and the findings of earlier studies pertaining to the subject of this study. This research discusses the basic concepts and scope of educational policy, types of educational problems, efforts to resolve educational problems with educational policy.